Tetrahydrofuran amino acids: Secondary structure in tetrameric and octameric carbopeptoids derived from a D-allo 5-(aminomethyl)tetrahydrofuran-2-carboxylic acid - Hungerford, N; Claridge, T; Watterson, M; Aplin, RT; Moreno, A; Fleet, G (2000)
The synthesis of a D-allo-5-(azidomethyl)tetrahydrofuran-2-carboxylate as an amino acid precursor (in which the carboxylic acid is cis to the azidomethyl substituent and trans to the diol moiety) is reported from D-ribose. The oligomerisation of this monomer to dimeric, tetrameric and octameric carbopeptoids is described. NMR studies into the solution structures of cyclohexylidene-protected oligomers and of a deprotected tetramer with eight free hydroxy groups are described. © The Royal Society of Chemistry 2000.